’’Glädjen är större än rädslan’’ - Kristoffersson, Fanny (2020)
This study examined adults’ experiences and perceptions about riding and fear and why they ride despite a feeling of fear. Equestrian sports are the eighth largest sport in Sweden with about half a million practitioners in all ages. Studies have shown physical and psychological advantages of riding but studies also show the existence of negative emotions. It is clear in studies that fear is a feeling that all equestrians feel sometimes, not seldom due to earlier falls where they hurt themselves. Despite of a sometimesstrong fear, equestrians still continue riding. Instructors regularly meet riders with fear. This study was built on focus group interviews where 18 adult equestrians distributed in four groups was interviewed about riding and fear. The result shows that equestrians could have a fear of falling off the horse, that they would hurt themselves or that the horse would get hurt. They were also afraid to lose control or to fail. Physical symptoms of fear could be shallow breathing, a high pulse and tense muscles which could cause a tense seat. Psychological symptoms of fear could be anxiety or a bad conscience. The fear could cause the equestrians to limit themselves which also limited the horse. Ways of handling the fear could be accepting it, admitting it and to talk about it. Surrounding themselves with people of whom they felt safe with also helped. The equestrians could also handle the fear by dismounting the horse when they felt afraid, despite of what they had learned. Instructors could handle their students fear by show that it is okay and normal to be afraid. The instructors could also show acceptance to make the student feel safe and teach from the riders’ and horses’ point of view. The equestrians continued riding despite a feeling of fear because of the lifestyle that followed and because the positive impact was bigger than the negative ones.